KESESUAIAN LOKASI DAN DAYA DUKUNG PULAU SAWO UNTUK MENDUKUNG WISATA KOTA PADANG, SUMATERA BARAT - Dhia Ul Hayat; Triyatno Triyatno (JURNAL BUANA, 2023)
The development of coastal ecotourism in the form of conservation of small islands, Sawo Island is one of the islands in the city of Padang. This study aims to analyze the suitability and carrying capacity of Sawo island tourism. The method used in this research is a field survey method. The results show that Sawo Island is very suitable for recreational tourism with a suitability index of 87.34%, with an area of ​​1.106,6 m2, the category of swimming tourism is very suitable for the suitability index 82.4% with an area of ​​2.993,5 m2 and quite appropriate 71.1%, for rides tourism. water category Very suitable, the index value is 84.38% with an area of ​​35,52 m2, quite suitable for the index is 68.75%, and according to the conditionality is 52.12%. The carrying capacity of swimming tours can accommodate 44 people, 120 people for swimming tours and 1 person for rides. Keywords : Carrying Capacity, Tourism, Sawo Island.